Virtue Ethics in the Letter to Titus An Interdisciplinary Study. Kontexte und Normen neutestamentlicher Ethik / Contexts and Norms of New Testament Ethics. Volume XII - Manomi, Dogara Ishaya 1985-; Johannes Gutenberg-Universität Mainz (Tübingen Mohr Siebeck, 2021)
Cover -- Title -- Dedication -- Acknowledgments -- Table of Contents -- List of Abbreviations -- List of Tables and Figures -- Chapter 1: Description of Concepts and Methodology -- 1.1 Authorship of the Letter to Titus: Hermeneutical and Methodological Implications -- 1.2 Locating the Premises of the Research -- 1.2.1 Inter-disciplinary Premise -- 1.2.2 Inter-cultural Premise -- 1.3 Virtue Ethics -- 1.3.1 General Description of Virtue Ethics -- 1.3.2 Historical Dimensions of Virtue Ethics -- 1.3.3 Neo-Aristotelian or Contemporary Virtue Ethics: What? Why? How? -- 1.3.4 Virtue Ethics in NT Ethics and Current Christian Ethics -- 1.3.5 Characteristics of Virtue Ethics -- 1.3.6 Working Definition of Virtue Ethics -- 1.4 Methodological Framework of the Research: From "Implicit Ethics" to "Exegethics" -- 1.5 The "Implicit Ethics" -- 1.5.1 The Linguistic Form -- 1.5.2 Norms or Maxims for Action -- 1.5.3 History of Traditions of Individual Norms -- 1.5.4 Values and the Priority of Values -- 1.5.5 Ethical Reflection/Generating Moral Significance -- 1.5.6 The Moral Agent(s) -- 1.5.7 Reflected Ethos -- 1.5.8 Addressee or Range of Application -- 1.6 Exegethics: An Adapted Version of the "Implicit Ethics" Methodology -- 1.6.1 Linguistic Form -- 1.6.2 Moral Agents -- 1.6.3 Ethical Reflection/Generating Moral Significance -- 1.6.4 History of Traditions of Individual Norms or Lexemes -- 1.6.5 Range of Application -- 1.7 Summary and Conclusion -- Chapter 2: History of Interpretation of the Selected Virtues in Titus -- 2.1 Σωφροσύνη: History of Interpretation -- 2.2 Δικαιοσύνη: History of Interpretation -- 2.3 Εὐσέβεια: History of Interpretation -- 2.3.1 Earlier Interpretations from Schlatter (1936) to Foerster (1971) -- 2.3.2 Other Earlier Interpretations not Reported by Marshall -- 2.3.3 Recent Interpretations from Marshall (1999) to Bray (2019).
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Hochschulschrift